KESALAHAN PENGGUNAAN TANDA BACA PADA KARANGAN EKSPOSISI SISWA KELAS X IIS-B SMA SWASTA KAMPUS TELUKDALAM TAHUN PEMBELAJARAN 2020/2021 - Faatulo Gulo; Askarman Laia; Kalvintinus Ndruru (Kohesi : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
The problem in this study was the error of using the punctuation on X-IIS B of SMA Swasta Kampus Telukdalam in the 2020/2021 that still didn't quite fit the general guidelines of the Indonesian spelling (PUEBI). The purpose of this study is to describe the error of using the punctuation on the student's expose essay. This research approach is qualitative work with a descriptive type. The source of the data in this study is a result of student exposure. Based on this study there 61 the errors use and the correct used is 43. The total number of punctuation used is 105. The most widely used punctuation errors are the stop mark it was 23 errors. Then the next one is the use of a coma sign on the student's exposed account that researchers found was 15 of the errors. Furthermore, the errors that the researcher found on the student's expose was hyphen mark with 11 errors. Next, the researchers have found the error in the used of the exclamation mark as many as 7. The last one is the researcher have found the error in the use of quotation marks with 5 errors. Based on the result it shows that in the writing of the student's expose the error can be occured because of the lack of punctuation, limited vocabulary and student inattention in writing the book of expose. The researcher's suggestion (1) for teachers, they should teach more the students about the use of the punctuation in the exposition essay and also expands the student vocabulary. (2) for students, they should enrich their vocabulary in order to be able to produce the good and correct writing